Acinar Gland Hyperplasia Masquerading as Pancreatic Head Carcinoma: A Case Report on a Diagnostic and Surgical Dilemma - Prima Maulana Cahyo Nugroho; Suryo Wahyu Raharjo (HM Publisher, 2025)
The preoperative differentiation of benign from malignant pancreatic head masses presents a significant clinical challenge. While pancreatic ductal adenocarcinoma (PDAC) is the primary concern, rare benign pathologies can be radiologically and clinically indistinguishable from cancer, leading to diagnostic uncertainty and complex surgical decisions. A 61-year-old male presented with a classic triad of obstructive jaundice, significant weight loss, and right upper abdominal pain. A contrast-enhanced computed tomography (CT) scan of the abdomen revealed a solid mass in the head of the pancreas, causing concomitant dilation of the common bile and pancreatic ducts—the